Impact of microfinance on rice production in Myanmar - AUNG, Swe Zin (KDI School, 2015)
Microfinance has emerged as a tool for reducing poverty in developing countries. Dr.Muhammad Yunus developed microfinance and he founded the Grameen Bank. In 2006, Yunus and Grameen Bank were awarded the Nobel Peace Prize for their work to promote economic and social development. Its main motivation is to contribute to proverty reduction by giving loans to poor people in Bangladesh and ultimately in the whole world. More than 70 percents of the total population reside in the rural areas and engaging in agricultural sector. Since the economy of Myanmar heavily depends on the agricultural sector, rural development is the fundamental concern for the country. Moreover, since rice is the staple food and the main export product of the country, rice production efficiency is an essential factor in the country. Although loans and some inputs subsides are provided to the farmers, the loan available to farmers is limited, and it covers only fews percent of total land area. Despite most research previously done on microfinance revealed positive impact, some studies argued negative impact of microfinance. This study analyses the impact of microfinance on small holder farmers who produce paddy with a case study. The data were analyzed based on a 100 sample farmers and they are divided into two groups, who access microfinance (Credit Beneficiaries) and another group cannot access (Non Credit Beneficiaries). T-test is applied to test the difference between mean rice production produced by two farmer groups. The linear regression model is used to analyze the impact of input variables which are used in rice production process. The study finds that microfinance largely contributed to rice production and also highlights the importance of microfinance and input variables on the production of rice. Additionally, credit beneficiaries group finds it relatively easy to access agricultural markets. Since credit constraints reduce the economic efficiency of farmers to produce rice it is recommended that formal private lending should be encouraged to ensure with fair interest rates.
Thesis(Master) --KDI School:Master of Development Policy,2015